INDIKATOR ENTOMOLOGI DAN RISIKO PENULARAN DEMAM BERDARAH DENGUE (DBD) DI PULAU JAWA, INDONESIA - Wiwik Trapsilowati, SKM, M.Kes; Yusnita Mirna Anggraeni; Mega Tyas Prihatin; Aryani Pujiyanti; Triwibowo Ambar Garjito (Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP) Salatiga, 2019)
One of dengue hemorrhagic fever (DHF) transmission risk factors is presence of vectors, especially Aedes aegypti. Vector surveillance is carried out to determine vectors distribution, vector density and risk of transmission. The larva survey is a common and easy vector surveillance method. This study aims to describe the cases and deaths due to DHF and entomological indicators in Java. This study was further analysis of Special Research Disease of Vector and Reservoir (Rikhus Vektora). Data collection was conducted in 2016 - 2018. The study locations were five provinces on Java Island i.e. East Jawa, West Jawa, Banten, DI Yogyakarta, DKI Jakarta and three districts were each taken. The data of DHF cases and entomology were analyzed descriptively. The results of the study show that the last two years were 50% districts experienced an increase in DHF cases and 38.9% an increase in deaths. The highest house index was 50% and lowest was 9%, highest larval free rate was 91% and lowest was 50%. The highest container index was 26.48%, lowest was 3.68%, and the highest breteau index was 67, lowest was 11. As many as 73.3% districts have the most water containers were buckets and 26.7% most water containers were bathtubs. Java Island has a medium to high potential region toward DHF transmission occurs. Increased knowledge and skills for eradication mosquito correctly by individually and community needs to be planned and implemented sustainable, to increase community participation as well.